Algorithmic Sighat in Blockchain Ecosystems: Formulating New Validity Standards for Smart Contracts in Contemporary Fiqh Muamalah - Nadiatul Maziyyah Attarwiyah; Abdul Rachman; Hendra Kholid (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2026)
The rapid development of smart contracts within blockchain technology has accelerated; however, their legal status in Islam still requires deeper normative inquiry. Existing literature has largely focused on technical efficiency, thereby leaving a research gap concerning the ontological shift in the structure of akad within fiqh muamalah. This study analyzes the validity of smart contracts from the perspective of contemporary fiqh muamalah. The data sources consist of primary literature on classical juristic principles and the frameworks of decentralized technology. This research employs a qualitative, normative-juridical method, using content analysis to examine the data. The findings reveal that: (1) Smart contracts transform the traditional concept of akad from static documents into self-executing algorithms that accurately fulfill the pillars of sighat (ijab–qabul), while simultaneously minimizing the potential for disputes (khushumah). (2) The transparent nature of blockchain inherently reduces elements of gharar (uncertainty), aligning with the principle of hifdz al-mal (protection of wealth). (3) This study formulates a new standard of validity that bridges classical juristic principles with decentralized systems. This study contributes to the development of a theoretical framework for Sharia-compliant digital contracts. It offers a strategic roadmap for regulators to adopt modern technology without compromising the substantive values of Islamic law.